Effect of heating duration on the synthesis of silicon carbide nanotubes by microwave heating of MWCNTs and silica - Voo, Tony Chung Sung; Voon, Chun Hong; Lee, Chang Chuan; Subash C.B. Gopinath,; Lim, Bee Ying; Mohd Khairuddin Mohd Arshad,; Foo, Kai Loong; Uda Hashim,; Ruslinda A. Rahim,; Mohd Nasha Ain Nordin,; Nor Azizah Parmin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this article, the effect of heating duration on the synthesis of silicon carbide nanotubes (SiCNTs) was reported. SiCNTs were synthesized from blend of silicon dioxide (SiO2) and multi-walled carbon nanotubes (MWCNTs) in the ratio of 1:3 by using the microwave heating at 1400°C and maintained at duration of 20, 40 and 60 min, respectively. SiCNTs synthesized at heating duration of 40 and 60 min showed the presence of single phase β-SiC in X-ray diffraction patterns. Meanwhile, field emission scanning electron microscope images showed that SiCNTs were formed and no residual of SiO2 and MWCNTs was observed for SiCNTs formed at heating duration of 40 and 60 min. Transmission electron microscopy images showed the SiCNTs have inter-planar spacing of 0.263 nm and tubular structure of nanotube were retained. The peak corresponded to β-SiC was observed at wavelength of 465 nm from the photoluminescence spectroscopy and associated with energy band gap of 2.67 eV. Absorption bands of Si-C bond were detected at 806.23 cm-1 from the Fourier transform infrared spectra. High purity SiCNTs was obtained at 40 and 60 min as indicated by low weight loss by thermo-gravimetric analysis. 40 min is the most suitable heating duration for the synthesis of single phase β-SiCNTs.